2021
DOI: 10.1016/j.ejrad.2021.109867
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 68Ga-DOTA-FAPI and 18FDG PET/CT imaging modalities in the detection of liver metastases in patients with gastrointestinal system cancer

Abstract: We aimed to compare the diagnostic performance of PET/CT imaging performed with 68Ga-DOTA-FAPI and 18FDG in detection of liver metastases in patients with gastrointestinal system (GIS) cancer. MethodsA total of 31 patients who underwent 68 Ga-DOTA-FAPI and 18 F-FDG PET/CT examinations and diagnosed with GIS cancer (15 colorectal, 9 pancreas, 4 stomach and 3 other cancers) were included in the study. The presence of liver metastasis was decided based on histopathologic diagnosis, PET/CT, other radiologic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(103 citation statements)
references
References 18 publications
5
86
2
Order By: Relevance
“…No additional studies were found screening the references of the selected articles. Finally, 26 articles (925 patients) including data on the comparison between radiolabeled FAPI and [ 18 F]F-FDG as PET radiotracers in oncology were included in the systematic review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The characteristics of the studies selected for the systematic review are presented in Table 1 , Table 2 , Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No additional studies were found screening the references of the selected articles. Finally, 26 articles (925 patients) including data on the comparison between radiolabeled FAPI and [ 18 F]F-FDG as PET radiotracers in oncology were included in the systematic review [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The characteristics of the studies selected for the systematic review are presented in Table 1 , Table 2 , Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Through the comprehensive computer literature search, 26 full-text articles including data on the head-to-head comparison of radiolabeled FAPI and [ 18 F]F-FDG in cancer patients were selected ( Table 1 ) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. All the selected articles were published in the last two years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations